Women academicians: gender and career progression - Michele Lunn (penerbit ukm, 2007)
This report is intended to provide a point for comparison between the experiences of women in Malaysia and the western feminist literature as it is interpreted by a woman situated within the New Zealand academic environment. My aim in undertaking this project is to investigate the process of negotiating the academic hierarchy. How does career progression take place and what factors do Malaysian academic women consider important? Utilising a qualitative methodology the research investigates the experiences of women at the early to mid stages of their academic careers focusing particularly on the process of establishing oneself within the university environment.